Bagaimana Fatherless Mempengaruhi Perkembangan Remaja?: Sebuah Tinjauan Konseling Analisis Transaksional - Hasanah, Uswatul; Basuki, Laura Ramadhani; Natasya, Trisna Dina; Al'Azizah, Arrozaqun Naura; Faktatisa, Isna Cahya; Prastiwi, Febri; Sitohang, Sabrina Queen; Putri, Dhini Ameylia; Azzahra, Nadinda Wilivia; Fidiawati, Pramulia (Kartika: Jurnal Studi Keislaman, 2026)
The phenomenon of the absence of a father's role in childcare (fatherless) is a social issue that is increasingly emerging in Indonesia and greatly affects adolescent development, especially in emotional, social, and behavioral aspects. This article aims to examine the influence of fatherlessness on adolescent development and analyze it through the perspective of Eric Berne's transactional analysis counseling. This research employs a library research method on relevant scientific articles from 2020 to 2025 indexed in Google Scholar. The findings indicate that adolescents experiencing fatherlessness tend to face emotional problems (anxiety, loneliness), low self-control, difficulties in social adjustment, and an increased risk of problematic behaviors such as juvenile delinquency. From a transactional analysis perspective, this condition is understood as an imbalance of ego states: a weak nurturing parent, a dominant and impulsive child, and an underdeveloped adult for decision-making. The transactional analysis counseling approach is seen as relevant to help adolescents experiencing fatherlessness increase self-awareness, strengthen the adult ego state, and build healthier interpersonal relationship patterns. It is hoped that these findings can serve as a conceptual basis for school counselors and educators in designing more targeted counseling services